PENGARUH PUPUK NPK PHONSKA TERHADAP PERTUMBUHAN DAN HASIL TUMPANG SARI CABAI (Capsicum annum L.) DAN BAWANG MERAH (Allium cepa L.) - Josina Irene Brigetha Hutubessy (Agriculture Faculty of Flores University, 2017)
Red chili (Capsicum annuum L.) is one of the vegetable commodities that has bright prospects and market demand continues to increase along with the increase in population, but until now the chili has not been able to meet the needs of the community. Efforts to increase production to meet needs that cover quality and quantity can be done by planting intercropping and fertilizing NPK Phonska. This study aims to determine the effect of NPK Phonska fertilizer on the growth and yield of intercropping of optimal chili and shallot plants. The experimental design used a Randomized Block Design (RBD) with a single factor pattern consisting of 5 NPK Phonska fertilizer treatments, namely BC0 = 0 kg ha-1 (control), BC1 = 300 kg ha-1, BC2 = 600 kg ha-1, BC3 = 900 kg ha-1, BC4 = 1200 kg ha-1. Non-destructive data collection is carried out. F test level 5% to test the effect of treatment, the difference between treatments was based on 5% BNT Value. The results showed that administration of NPK Phonska fertilizer had a very significant effect on chili plants, namely on growth variables and yields of plant height 26.14 cm, number of leaves of 15.11 strands, leaf area of ??11.86 cm2 and plant high onion 33, 34 cm, number of leaves 33.14 strands. The optimum dose of NPK Phonska fertilizer which provides optimal growth and yield of intercropping of chili and shallot plants is 1200 kg ha-1.